Ecosystem services and multifunctionality are co-regulated by biotic and abiotic factors along with forest types in a temperate forest of South Korea - Min-Ki Lee; Yong-Ju Lee; Jung-Hwa Chun; A-Reum Kim; Chang-Bae Lee (Global Ecology and Conservation)
Given global issues such as large-scale deforestation and increasing habitat loss, promoting forest ecosystem multifunctionality (EMF) is essential for the successful implementation of global sustainable development. This study aims to quantify the four ecosystem service categories (i.e., provisioning, regulating, cultural, and supporting) and the ability to comprehensively provide them, EMF, based on 18 ecosystem services-related variables. Additionally, we evaluated the influence of biotic (i.e., species diversity, functional dominance, stand structural diversity) and abiotic (i.e., topography, climate, and soil) factors, and stand age on EMF and each ecosystem service category. We collected data from 98 plots, each 20 × 20 m, across the seven major forest types of Mt. Gariwang, which is a representative temperate forest in South Korea. Multimodel averaging and piecewise structural equation modeling were used to identify key variables influencing EMF and ecosystem service categories and to assess their interrelationships. Our results show that higher plant species richness and older forest stands enhanced stand structural diversity, which directly and positively affected EMF. EMF is primarily driven by biotic factors, such as the community weighted mean of traits, rather than abiotic factors. The mechanisms influencing each ecosystem services differed. Variance partitioning analysis revealed that the relative contributions of the four ecosystem service categories to the EMF are similar, with supporting and regulating services categories showing significant negative and positive effects on EMF, respectively. These findings suggest that forest management should comprehensively consider stand age and structural diversity to enhance EMF and as well as individual ecosystem service category. Furthermore, management practices that promote functional traits, such as wood density and leaf nitrogen content, are essential for increasing EMF. Finally, the degree of control of ecosystem service categories over EMF varies across forest types, so a clear management plan must be developed for each forest type.